Role of mast cells in the pathogenesis of liver fibrosis in nonalcoholic fatty liver disease - Lewandowska, Ewa; Wosiak, Agnieszka; Zieliński, Andrzej; Brzeziński, Piotr; Strzelczyk, Janusz; Szymański, Dariusz; Kobos, Józef (Polish Journal of Pathology, 2020)
Nonalcoholic fatty liver disease (NAFLD), a very common comorbidity of obesity, may progress from simple steatosis to nonalcoholic steatohepatitis and liver cirrhosis. The aim of this study was to determine whether mast cells (MCs) participate in the pathogenesis of liver fibrosis in patients with NAFLD. Liver specimens collected either from obese subjects or the control group were prepared for histological examination. The patients were divided into groups depending on inflammation and fibrosis grade, and the mean total number of mast cells/mm2 and those located only in portal areas/ fibrous septa or within lobules were calculated for each grade. Mast cells were detected by pina-cyanol erythrosinate staining. There was a strong positive correlation between the number of mast cells, especially those located within portal areas and fibrous septa, and the liver fibrosis grade (r = 0.736, p < 0.0001). No similar dependency between the number of mastocytes within lobules and liver fibrosis grade was identified. The results from this study suggest the involvement of mast cells from portal areas and fibrous septa in the pathogenesis of liver fibrosis in patients with NAFLD.